Effect of Heated Red Bean Pillow Application for College Women with Dysmenorrhea - Jeung Im Kim (Korean Society of Women Health Nursing, 2013)
PURPOSE: Dysmenorrhea is a menstrual condition characterized by severe and frequent cramps and pain. Effective treatment methods for dysmenorrhea are not yet fully understood. This research compares the effects of pain killers and heated red bean pillows. METHODS: Data were got on demographic data, menstrual cycle status, and activities of daily living (ADLs) limitations, dysmenorrhea severity and menstrual pain scores. Following a 10% drop-out rate, 44 young women satisfied the inclusion criteria. To prevent any bias, the experimental and control groups were selected from different campuses. We used two sizes of red bean pillows: 15x18 cm, weighing 400g; and 13x11.5 cm, weighing 220g. For analysis, we used IBM SPSS statistics 19.0. RESULTS: Ninety-nine point seven percentage of total subjects reported moderate to severe dysmenorrhea and 63.6% reported as moderate to severe daily activities limitations. The mean pain score with visual analogue scale was 80.2+/-9.42 of 100 and 86.4% used pain killers to alleviate menstrual discomfort in all the subjects. In both groups, all three variables showed significant improvement and the Moos's Menstrual Distress Questionnaire (MDQ) scores changed significantly between menstrual and post-menstrual time point at within groups and not significantly different at premenstrual and menstrual time point at between groups. However, the MDQ score was significantly higher in experimental group than control group at post-menstruation time point and the degree of satisfaction was higher in the control group. CONCLUSION: This research shows that red-bean pillows on the abdomen are effective in assisting the ADL and diminishing pain severity. With regard to its safety the study indicates it can be a convenient and safe option for female students with menstrual discomfort in schoolas a non-pharmacological self-help.